Epitaxial silicon membranes - BASSOUS; ERNEST; URAM; KEVIN J; MEYERSON; BERNARD S (1994)
The subject invention provides a silicon membrane material made from silicon that is epitaxially deposited at low temperatures greater than or equal to 500 DEG C. and doped with controlled amounts of boron and germanium. A silicon membrane structure is provided and made by one or more layers of ultra thin epitaxially deposited silicon layers that are precisely controlled in both thickness and composition. At least one of the layers is doped with boron in a concentration range greater than 2x1020 atoms of boron per cubic centimeter of silicon, or with germanium in a concentration range greater than 5x1020 atoms of germanium per cubic centimeter of silicon, or with a combination of boron and germanium in these concentration ranges. A silicon membrane fabrication process is also provided which requires no additional masking film to protect the membrane surface during KOH etching of the bulk silicon substrate.